2016
DOI: 10.1111/eip.12346
|View full text |Cite
|
Sign up to set email alerts
|

Coping power for preschool‐aged children: a pilot randomized control trial study

Abstract: The results of this study are promising and can be interpreted as providing initial support for the efficacy of the preschool version of Coping Power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Although two previous studies indicated the capacity of the CPU for preschoolers to reduce children's behavioral problems (Muratori et al, 2017b(Muratori et al, , 2019a, this is the first study that investigated the efficacy of the CPU in promoting better pre-academic skills using standardized tests.…”
Section: Testing the Efficacy Of Coping Power Universal On Behavioral...mentioning
confidence: 93%
“…Although two previous studies indicated the capacity of the CPU for preschoolers to reduce children's behavioral problems (Muratori et al, 2017b(Muratori et al, , 2019a, this is the first study that investigated the efficacy of the CPU in promoting better pre-academic skills using standardized tests.…”
Section: Testing the Efficacy Of Coping Power Universal On Behavioral...mentioning
confidence: 93%
“…Dissemination studies of CP have also provided support for its effectiveness when implemented by intensively trained school counselors (Lochman et al, 2009;Lochman et al, 2012), when delivered to students in an individual format (Lochman et al, 2015), and when adapted for use with early adolescents (Lochman et al, 2017). Positive results have also been documented for CP in international settings (Muratori et al, 2015;Muratori et al, 2017;Mushtaq, Lochman, Tariq, & Sabih, 2016;van de Wiel et al, 2007;van de Wiel, Matthys, Cohen-Kettenis, & van Engeland, 2003;Zonnevylle-Bender, Matthys, van de Wiel, & Lochman, 2007). An abbreviated version of CP (24 child sessions and 10 parent sessions) implemented over 1 year has also reduced teacherrated externalizing behavior (Lochman, Boxmeyer, Powell, Roth, & Windle, 2006), with results sustained at a 3-year follow-up (Lochman, Baden, et al, 2014).…”
Section: Tier 2 Identification and Interventionsmentioning
confidence: 94%
“…Principles and practices of the original CPP were preserved but the activities of the CPU program for pre-schoolers are modified to be developmentally appropriate for pre-school children (see Intervention section). A previous Randomized Control Trial study (164 pre-schoolers) showed that children in a CPU condition had lower levels of behavioral difficulties than children in a control condition (Muratori et al., 2016a).…”
Section: The Coping Power Universalmentioning
confidence: 98%